Novel Hydrogen Peroxide Sensor Based on Chitosan-Ag Nanoparticles Electrodeposited on Glassy Carbon Electrode - Zhang, Mei; Song, Yonghai; Wang, Li; Wan, Lingli; Xiao, Xianping; Ye, Shuhong (Asian Journal of Chemistry, 2011)
A sensitive, simple and economically cheap hydrogen peroxide (H2O2) sensor was developed by electrodepositing Ag nanoparticles in the presence of chitosan on a glassy carbon electrode (GCE). Atomic force microscopy results showed that the Ag nanoparticles was small as compared to Ag nanoparticles on bare GCE and exhibited a narrow size distribution. The electrochemical experiments showed that this chitosan-Ag nanoparticles/GCE had a good catalytic ability toward the reduction of H2O2. The effects of deposition potential, deposition time to the concentration of chitosan for Ag nanoparticles formation and the pH of the electrolyte solution on the electrocatalytic reduction of H2O2 were also investigated. Under the optimal conditions, the sensor exhibited a linear range of 1.0 μM to 8.6 mM with the detection limit of 0.24 μM. A rapid response of the sensor could achieve 95 % of the steady-state current in less than 2 s. This sensor with a high selectivity and sensitivity was expected to use for practical applications in detecting H2O2.